Temperature Dependence of the Electron Paramagnetic Resonance Spectrum of Asphaltenes from Venezuelan Crude Oils and Their Vacuum Residues - Hernandez Nuñez, Maury Sabrina (2019)
The electron paramagnetic resonance (EPR) technique is used to evaluate the temperature dependence of the aggregation processes in asphaltenes of heavy and extra-heavy crude oils and their vacuum residues from the Venezuelan Oil Belt. All of the EPR spectra of the samples studied show an intense central signal assigned to free radicals (FRs) and a multiplet as a result of the presence of a V+ 4 porphyrin. From the analyses of the inverse of the normalized area as a function of the temperature for the FR signal and the most intense peak in the vanadium multiplet, we obtain a set of temperatures related to the transition of fast-to-slow motion regions, the temperature of generation-recombination of FRs, and the cracking temperature in all of the samples. On the other hand, applying a Curie-Weiss law, we obtain the order-disorder temperatures and correlated them with the American Petroleum Institute grade of the samples. A computational simulation was performed to propose possible conformers based on the experimental data to confirm our results, which can be used as a probe of the structural and conformational changes in the asphaltene structure.